characterization and biological activity of some new tetra - azo compounds - Muzael, Maged (University of Thi-Qar Journal of Science, 2008)
In this paper , preparation and characterization of some tetra azo compounds .Azo coupling of 3`,3,4`,4- tetra amino biphenyl with phenol and some phenol derivatives in alkaline solution gave azo dyes. I.R and U.V. visible spectra were recorded to identify the three azo compounds prepared . Some physical and chemical properties such as molar absorption coefficient in different pH value and maximum absorption λ maxwere investigated. The biological effect of these dye against two gram positive Bacteria (S.aureuse) and other two gram negative Bacteria (P.aeruginosa) is presented .